Magnetic Field Calculation under Normal and Abnormal Conditions of Overhead Transmission Lines - Nagat M. K. Abdel-Gawad; Adel Z. El Dein; Mohamed Magdy (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
Ground level magnetic field from overhead transmission lines (OHTLs) is of increasingly important considerations in several research areas due to their harmful effect on human health and environment. This paper computes the ground level magnetic field, under normal and abnormal conditions of Egyptian 500-kV single circuit transmission line, in three dimension (3-D) coordinates by using 3-D integration technique. Abnormal conditions include symmetric fault, un-symmetric faults, direct stroke, and indirect stroke on the OHTL. Where, ATP software is used to simulate the OHTL under all faulty and lightning conditions. Varying time magnetic fields under normal and abnormal conditions, at certain points that located at mid-span, tower height and right-of-way (ROW), are also computed that to indicate the worst case. DOI : http://dx.doi.org/10.11591/telkomnika.v12i5.5151